Élaboration d'une échelle de mesure de la motivation dans un dispositif de cours en ligne ouvert et massif (EMOC-CLOM) en contexte francophone - Mejdi Ayari; Beatrice Mabilon-Bonfils; Laurent Jeannin (Centre National d'Enseignement à Distance, 2023)
By referring to the theory of self-determination, this research proposes the construction of a scale for measuring motivation in the context of open and massive online courses (EMOC-CLOM) in a French-speaking context. Two data collections were carried out (N= 659 and 324) with learners enrolled in the MOOC "Prepare and pass DELF B2 and DALF C1" at the University of Jendouba (Tunisia). We propose a scale of 16 items around four motivational variables: intrinsic motivation, extrinsic motivation with identified regulation, extrinsic motivation with external regulation and amotivation. The results of the various statistical analyses, in accordance with the Churchill protocol, have shown that the proposed scale meets the commonly accepted reliability criteria.